2021
DOI: 10.3390/e23020225
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Specific Network for Personalized Breast Cancer Therapy with Multi-Omics Data

Abstract: The development of new computational approaches that are able to design the correct personalized drugs is the crucial therapeutic issue in cancer research. However, tumor heterogeneity is the main obstacle to developing patient-specific single drugs or combinations of drugs that already exist in clinics. In this study, we developed a computational approach that integrates copy number alteration, gene expression, and a protein interaction network of 73 basal breast cancer samples. 2509 prognostic genes harborin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…The majority of studies relied on the application of metabolomics-based approaches in BC tissue [141,143] and serum [140,142,144] samples, although groups have evaluated transcriptomic [33,45] and proteomic [146] profiles in tissue samples. Various studies have described how the combination of omics approaches could characterize specific targets and foster the development of novel therapeutic strategies for specific subgroups of BC patients [147][148][149]. In particular, multi-omics studies have focused on identifying and validating metabolic enzymes as promising therapeutic strategies for the treatment of different BC tumors (Table 4).…”
Section: Multi-omics Studies and Novel Bc Treatment Strategiesmentioning
confidence: 99%
“…The majority of studies relied on the application of metabolomics-based approaches in BC tissue [141,143] and serum [140,142,144] samples, although groups have evaluated transcriptomic [33,45] and proteomic [146] profiles in tissue samples. Various studies have described how the combination of omics approaches could characterize specific targets and foster the development of novel therapeutic strategies for specific subgroups of BC patients [147][148][149]. In particular, multi-omics studies have focused on identifying and validating metabolic enzymes as promising therapeutic strategies for the treatment of different BC tumors (Table 4).…”
Section: Multi-omics Studies and Novel Bc Treatment Strategiesmentioning
confidence: 99%
“…Recently, more and more studies showed that genomic aberrations are key events in the progression from normal to tumoral tissue [6,7]. In addition, to investigate the crucial role of genomic alterations and gene expression profiles in disease progression, some studies reported novel candidate genes by integrating gene expression and CNA profiles [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…A network propagation analysis was used to reposition drugs based on a drug-pathway network, where pathways for each drug were identified by an enrichment analysis of the genes regulated by each drug using the Connectivity Map (CMAP) for the drug’s phenotypic profile [ 24 ]. Moreover, computational methods with diverse molecular data types were developed to identify therapeutic targets for BC [ 25 ]. These methods considered breast cancer in general without considering its subtypes and did not address the heterogeneity of BC.…”
Section: Introductionmentioning
confidence: 99%